The long way to establish the ergogenic effect of caffeine on strength performance: an overview review - Giráldez-Costas, V.; Del Coso, J.; Mañas, A.; Salinero, J. J. (Nutrients, 2023)
This overview review aimed to describe the evolution of the characteristics of the research on caffeine effects on strength. A total of 189 experimental studies with 3459 participants were included. The median sample size was 15 participants, with an over-representation of men vs. women (79.4 vs. 20.6%). Studies on young participants and elders were scarce (4.2%). Most studies tested a single dose of caffeine (87.3%), while 72.0% used doses adjusted to body mass. Single-dose studies ranged from 1.7 to 7 mg/kg (4.8 ± 1.4 mg/kg), while dose-response studies ranged from 1 to 12 mg/kg. Caffeine was mixed with other substances in 27.0% of studies, although only 10.1% of studies analyzed the caffeine interaction with these substances. Capsules (51.9%) and beverages (41.3%) were the most common forms of caffeine administration. Similar proportions of studies focused on upper (24.9%) or lower body strength 37.6% (37.6% both). Participants` daily intake of caffeine was reported in 68.3% of studies. Overall, the pattern in the study of caffeine`s effects on strength performance has been carried out with experiments including 11-15 adults, using a single and moderate dose of caffeine adjusted to participants` body mass in the form of a capsule.